Global modernity, consumerism and individualism in Latin America. Theoretical perspective - Mejía Navarrete, Julio (2017)
The study explores the profound transformations of modernity of the XXI century. Individualism and consumerism in its institutional and cultural diversity, project start to delineate society and new forms of colonialism in the population of Latin America it stands out. The article aims to develop some theoretical issues at the fundamentals of the changes in contemporary social order.